Drug interactions (Anales de la Real Academia de Medicina y Cirugía de Valladolid, 2023)
The ancient therapeutics very often used complex associations in a prescription that it was difficult to guess the effect that could be obtained from them, also presenting very dangerous drug interactions. At the beginning of our century came a reaction against this absurd polypharmacy. Huchard, in 1909, said: "I advise not to use more than one drug at a time, be it alkaloid or glycoside, whose physiological and therapeutic action is well known to you... Beware of medicinal associations, which can oppose the physiological and therapeutic action, that are still capable of producing very similar and useless mixtures, when not dangerous”. Drug interactions can be classified as follows: interactions outside the body (physical and chemical incompatibilities), pharmacokinetic interactions. pharmacodynamic and therapeutic interactions, nutrient-drug interactions.
Keywords: : pharmacokinetics; interaction; drugs.